(untitled) (Global Journal of Management and Business Research, 2021)
The study investigated environmental accounting disclosure and financial performance of listed multinational companies in Nigeria. This study was conducted by firstly assessing the level of compliance, and then exploring the effect of environmental disclosure on financial performance with a focus on multinational companies in the face of continued environmental abuse witnessed in the Nigerian business space owing to the non-availability of sustainability reporting legal framework. The study used secondary data obtained from the published annual reports of the companies from 2011 to 2020.